Cu2+-Regulated reversible coordination interaction of GQD@Tb/GMP ICP nanoparticles: towards directly monitoring cerebrospinal acetylcholinesterase as a biomarker for cholinic brain dysfunction. Issue 24 (14th October 2020) - Liu, Chang; Huang, Chunyu; Ma, Ruixue; Zhai, Wanying; Deng, Jingjing; Zhou, Tianshu
Abstract : Based on the rational design of the Cu 2+ -regulated reversible coordination interaction of GQD@Tb/GMP ICPs, a new turn-on fluorescence strategy is developed for monitoring AChE in CSF as a biomarker for cholinic brain dysfunction-related disease. Abstract : This work demonstrates a new strategy for sensing cerebrospinal acetylcholinesterase (AChE) as a cholinergic biomarker for brain dysfunction based on graphene quantum dot (GQD)-functionalized lanthanide infinite coordination polymer (Ln-ICP) nanoparticles. The ICPs used in this work were comprised of two components, i.e. a supramolecular Ln-ICP host formed by the coordination between the GMP ligand and central metal ion Tb 3+, and guest GQDs with abundant functional groups, which were utilized as antenna ligands to further sensitize the fluorescence of Tb/GMP. Upon excitation at 300 nm, the obtained GQD@Tb/GMP ICP nanoparticles exhibited enhanced green fluorescence from Tb/GMP. With the addition of Cu 2+, the competitive coordination between Cu 2+ and GQDs weakened the antenna effect, leading to a decrease in the fluorescence of GQD@Tb/GMP ICPs. However, in the presence of thiocholine (TCh), a thiol-containing compound hydrolyzed from acetylthiocholine (ATCh) by AChE, a stronger coordination interaction between Cu 2+ and TCh occurred, resulting in the restoration of the fluorescence of GQD@Tb/GMP ICPs. Using the method established herein, the cerebrospinal AChE fluctuation of rats with acute organophosphorus pesticide (OP) poisoning or chronic Alzheimer's disease (AD) could be monitored. This study essentially provides a novel approach to realize the direct monitoring of a biomarker for brain dysfunction by regulating the competitive coordination interaction reversibly, which is critical in the early diagnosis and therapy of brain diseases.